Mini Riset Uji Fisik Sederhana Keefektifan Eco-enzyme untuk Pencemaran Air - Rivatri Julianti Karila; Muhyiatul Fadilah; Rahmawati Darrusyamsu; Siska Alicia Farma; Rahmadhani Fitri; Ganda Hijrah Selaras (Institut Agama Islam Negeri Kerinci, 2022)
Water is a component that plays an important role in life on earth. Water that used for everyday life is also has a standard for its quality. However, the availability of water with suitable quality is difficult to obtain. This is due to water pollution originating from human activities, making the water quality decline and unfit for use. Therefore, the problem of water pollution needs special attention. Recently, practiciorurs were found a solution toafound to overcome the pollution, one of which is by using eco-enzyme. This study discusses a simple procedure in the form of physical observation to determine the effectiveness of eco-enzyme for water pollution. The results showed that Eco-enyzme is effectiveness in overcoming water pollution by changes in smell, color, and turbidity. Keyword : Eco-enzyme, Physical Observation, Water Pollution